A trusted subject architecture for multilevel secure object-oriented databases - Thomas, R.K.; Sandhu, R.S. (IEEE transactions on knowledge and data engineering, 1996)
We address security in object-oriented database systems for multilevel secure environments. Such an environment consists of users cleared to various security levels, accessing information labeled with varying classifications. Our purpose is three-fold. First, we show how security can be naturally incorporated into the object model of computing so as to form a foundation for building multilevel secure object-oriented database management systems. Next, we show how such an abstract security model can be realized under a cost-effective, viable, and popular security architecture. Finally, we give security arguments based on trusted subjects and a formal proof to demonstrate the confidentiality of our architecture and approach. A notable feature of our solution is the support for secure synchronous write-up operations. This is useful when low level users want to send information to higher level users. In the object-oriented context, this is naturally modeled and efficiently accomplished through write-up messages sent by low level subjects. However, such write-up messages can pose confidentiality leaks (through timing and signaling channels) if the timing of the receipt and processing of the messages is observable to lower level senders. Such covert channels are a formidable obstacle in building high-assurance secure systems. Further, solutions to problems such as these have been known to involve various tradeoffs between confidentiality, integrity, and performance. We present a concurrent computation model that closes such channels while preserving the conflicting goals of confidentiality, integrity, and performance. Finally, we give a confidentiality proof for a trusted subject architecture and implementation and demonstrate that the trusted subject (process) cannot leak information in violation of multilevel security.